Ordinance no. 25, §§ 1-3, Lamont Town Council (1911) (Lamont, Washington). - (:unkn) unknown (General Publisher, 1911)
It shall be unlawful for any person except officers of the Law, Police Officers and other persons whose duty it is to execute process or warrants or make arrests, to carry upon his person any concealed weapon, consisting of either a revolver, pistol, or other fire-arm, or any knife, (other than an ordinary pocket knife), or any dirk, dagger, sling-shot, or metal knuckles, or any instrument by the use of which injury could be inflicted upon the person or property of any other person.
--
Keywords: CARRY - CONCEALED